A)
[tex]x^2+7x-12=0\\ \Delta=7^2-4*1*(-12)=49+48=97\\ \sqrt{\Delta}=\sqrt{97}\\ x_1=\frac{-7-\sqrt{97}}{2}} \\ x_2=\frac{-7+\sqrt{97}}{2}} [/tex]
B)
[tex]x^2-7x+12=0\\ \Delta=(-7)^2-4*1*12=49-48=1\\ \sqrt{\Delta}=1\\ x_1=\frac{7-1}{2}}=3 \\ x_2=\frac{7+1}{2}} =4[/tex]
C)
[tex]-x^2+7x+12=0\\ \Delta=7^2-4*(-1)*12=49+48=97\\ \sqrt{\Delta}=\sqrt{97}\\ x_1=\frac{-7-\sqrt{97}}{-2}}=\frac{7+\sqrt{97}}{2}} \\ x_2=\frac{-7+\sqrt{97}}{-2}} =\frac{7-\sqrt{97}}{2}}[/tex]
D)
[tex](x+3)(x+4)=0\\ x+3=0 \vee x+4=0\\ x=-3 \vee x=-4[/tex]